STRATEGI INOVASI DALAM RANGKA MENJAGA KEBERLANJUTAN BISNIS DALAM MENGHADAPI ERA VOLATILITY, UNCERTAINTY, COMPELXITY, DAN AMBIGUITY (VUCA) - Aribowo, Handy; Wirapraja, Alexander (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2018)
Currently, all the nations of the world are facing competition inthe era of Volatility, Uncertainty, Complexity, and Ambiguity, whichrequired an innovation strategy in order to support businesssustainability. The methodology used in this research is the study ofliterature with the results of research, among others, Indonesia mustincrease the output of innovation, the implementation of innovation inorder to support business sustainability need to strengthen research anddevelopment and utilize technological progress as a means to innovateand innovate in the company, leaders are very influential is needed inencouraging the birth of various innovations, with the innovationmindset owned by the leader will be born a culture of innovation in thecompany.